2010
DOI: 10.1186/1750-1326-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin carboxy-terminal hydrolase L1 (UCHL1) S18Y polymorphism in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is characterized by protein aggregates, i.e. senile plaques and neurofibrillary tangles. The ubiquitin-proteasome system has been proposed a role in proteolytic removal of these protein aggregates. Ubiquitin carboxy-terminal hydrolase L1 (UCHL1) is a de-ubiquitinating enzyme with important functions in recycling of ubiquitin. The S18Y polymorphism of the UCHL1 gene confers protection against Parkinson's disease. In this study, the genotype and allele frequencies of the UCHL1 S18Y polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Increased association of UCHL1 with the membrane fraction due to farnesylation has also been reported in Parkinson's disease and was shown to mediate alpha‐synuclein toxicity in cells []. While certain polymorphisms in UCHL1 are reported to be protective in Parkinson's disease, this protective effect is not seen in AD []. Given that UCHL1 appears to play a role in many neurodegenerative diseases, it is likely not specific to AD; however, that does not negate the fact that it may also play an important role in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased association of UCHL1 with the membrane fraction due to farnesylation has also been reported in Parkinson's disease and was shown to mediate alpha‐synuclein toxicity in cells []. While certain polymorphisms in UCHL1 are reported to be protective in Parkinson's disease, this protective effect is not seen in AD []. Given that UCHL1 appears to play a role in many neurodegenerative diseases, it is likely not specific to AD; however, that does not negate the fact that it may also play an important role in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the 5 SNPs studied here were in Hardy-Weinberg equilibrium and our LD analysis suggests that the gene consists of one LD block. Two previous studies showed no association between the UCHL1 S18Y polymorphism and Caucasian AD [15,18]. However, a study by Xue and Jia [19] on a Han Chinese population found that the Y allele of the polymorphism might have a protective effect for female AD cases only.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of common UCHL1 polymorphisms on AD has not been fully explored either. Several studies on the relationship between S18Y and AD have been carried out, but its effect on AD is still unresolved [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Tau is a highly soluble microtubule associated protein whose main function is to bind to microtubules, promoting their assembly and stability (35). Following injury, it is cleaved by calpain-1 and 3, becomes insoluble and forms aggregates, known as neurofibrillary tangles (80). Such tau inclusions were identified in numerous degenerative diseases, which were collectively named tauopathies (79).…”
Section: Introductionmentioning
confidence: 99%